Advancing the Implementation of Coastal Restoration in Louisiana Through a Co-production of Science Framework - Jacob M. Oster; Jessica R. Henkel; Alyssa Dausman; Eva D. Windhoffer; Bingqing Liu; Melissa M. Baustian; Denise Reed; Summer Langlois; David C. Lindquist (Estuaries and Coasts, 2025)
Coastal Louisiana faces complex challenges from the compounding effects of coastal land loss and climate change. The State of Louisiana’s Coastal Protection and Restoration Authority (CPRA) and the RESTORE Act Center of Excellence for Louisiana (LA-COE) have adopted a co-production of science framework to help ensure that scientific research funded through the LA-COE supports the research needs of CPRA and the Louisiana Coastal Master Plan (CMP), a large-scale coastal restoration plan that outlines activities needed to restore and protect Louisiana’s coast. In this paper, we describe the co-production of science framework established between the LA-COE, CPRA, and research projects funded by the LA-COE. Through an iterative process, the Louisiana CMP is revised every 6 years with improved model and scientific information. The LA-COE leverages the cyclical nature of the CMP by working with CPRA to identify research needs for each Request for Proposals solicited by the LA-COE. The LA-COE proposal review process is structured to include anonymous CPRA review of projects to promote the production of actionable science, and once funded, multiple mechanisms are in place to support collaboration between researchers and CPRA staff. We highlight these mechanisms and provide examples of four LA-COE-funded projects where co-produced science is being used by CPRA to inform the CMP and its implementation. Finally, we discuss challenges of co-production within the confines of funding requirements and review restrictions, highlighting how the LA-COE continues to adapt to navigate these challenges and enhance the implementation of co-production throughout the research funding lifecycle.

Leveraging co-production within ecosystem restoration to maximize benefits to coastal birds - Eva D. Windhoffer; Tim J.B. Carruthers; Jessica Henkel; Jeffrey S. Gleason; Jon J. Wiebe (Journal of Environmental Management, 2024)